2000
DOI: 10.2337/diacare.23.7.928
|View full text |Cite
|
Sign up to set email alerts
|

Influences on day-to-day self-management of type 2 diabetes among African-American women: spirituality, the multi-caregiver role, and other social context factors.

Abstract: OBJECTIVE -Many African-American women are affected by diabetes and its complications, and culturally appropriate lifestyle interventions that lead to improvements in glycemic control are urgently needed. The aim of this qualitative study was to identify culturally relevant psychosocial issues and social context variables influencing lifestyle behaviors-specifically diet and physical activity-of southern African-American women with diabetes.RESEARCH DESIGN AND METHODS -We conducted 10 focus group interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(233 citation statements)
references
References 13 publications
7
223
0
3
Order By: Relevance
“…Samuel-Hodge and colleagues [83] conducted focus group interviews with African-American women with type 2 diabetes, and learned that their multiple caregiving responsibilities often interfered with managing their own illnesses. Participants in this qualitative study reported that faith and spirituality were important and under-recognized coping mechanisms for people living with chronic disease.…”
Section: Health Literacy and Patient Adherencementioning
confidence: 99%
“…Samuel-Hodge and colleagues [83] conducted focus group interviews with African-American women with type 2 diabetes, and learned that their multiple caregiving responsibilities often interfered with managing their own illnesses. Participants in this qualitative study reported that faith and spirituality were important and under-recognized coping mechanisms for people living with chronic disease.…”
Section: Health Literacy and Patient Adherencementioning
confidence: 99%
“…In an Iranian study, the patients regarded the physician as 'holy men' 5 . The influence of relatives has been shown to play a major role in supporting patients with chronic illness and specifically diabetes 6,7 . Evidence showed that partners had shared the same burden with diabetes patients, especially if the partners were women 8 .…”
Section: Study Selectionmentioning
confidence: 99%
“…Em 17 pesquisas foram utilizados softwares para análise de dados qualitativos, com destaque para o Ethnograph (Arcury et al, 2004;Broom, Whittaker, 2004;Savoca, Miller, Quandt, 2004;MercadoMartinez, Ramos-Herrera, 2002;Liburd et al, 1999) e o NUD.IST (Lawton et al, 2005;Sarkadi, Rosenqvist, 2003;Daaleman, Cobb, Frey, 2001;Samuel-Hodge et al, 2000;Loewe et al, 1998), seguidos pelo Atlas.ti (Cabassa et al, 2008;Lutfey, Freese, 2007) e pelo NVivo (Polzer, Miles, 2007;Lawton, Peel, Parry, 2008).…”
Section: Metamétodounclassified